2023
DOI: 10.3389/fpsyt.2022.1082052
|View full text |Cite
|
Sign up to set email alerts
|

Desynchronized white matter function and structure in drug-naive first-episode major depressive disorder patients

Abstract: BackgroundMajor depressive disorder (MDD) is a highly prevalent mental disease. Using magnetic resonance imaging (MRI), although numerous studies have revealed the alterations in structure and function of grey matter (GM), few studies focused on the synchronization of white matter (WM) structure and function in MDD. The aim of this study was to investigate whether functional and structural abnormalities of WM play an essential role in the neurobiological mechanisms of MDD.MethodsGradient-echo imaging sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…However, multiple reports have demonstrated successful detection and analysis of BOLD signals in white matter ( 11 , 12 ). For example, previous studies have reported white matter BOLD signal responses to tasks and at rest ( 13 16 ), relationships between white matter signals and the gray matter regions to which they connect ( 17 19 ), alterations of white matter BOLD signal in disease/disorder ( 20 25 ), and finally, robust, reproducible network properties of white matter BOLD signals ( 18 , 26 ). Importantly, recent reports have confirmed that white matter responses to stimuli are similar to, but different from, those in gray matter ( 13 , 14 , 27 , 28 ), generally indicating a slower response, smaller percent signal change, and variation across regions ( 29 ).…”
mentioning
confidence: 99%
“…However, multiple reports have demonstrated successful detection and analysis of BOLD signals in white matter ( 11 , 12 ). For example, previous studies have reported white matter BOLD signal responses to tasks and at rest ( 13 16 ), relationships between white matter signals and the gray matter regions to which they connect ( 17 19 ), alterations of white matter BOLD signal in disease/disorder ( 20 25 ), and finally, robust, reproducible network properties of white matter BOLD signals ( 18 , 26 ). Importantly, recent reports have confirmed that white matter responses to stimuli are similar to, but different from, those in gray matter ( 13 , 14 , 27 , 28 ), generally indicating a slower response, smaller percent signal change, and variation across regions ( 29 ).…”
mentioning
confidence: 99%